The Effectiveness of Using English Movie with English Subtittles in Teaching Vocabulary at the Eighth Year Students Of SMPN 1 Selong in the Academic Year of 2018/2019 - Husnul Lail (Journal of Languages and Language Teaching, 2019)
This investigation was aimed to identify the effectiveness of using English movie with English subtitles in teaching vocabulary in the form comprehension of descriptive text at the eighth year students of SMPN 1 Selong Lombok Timur in the academic year of2018/2019. Learning out comes in this research included learning achievement in the form of cognitive skill and vocabulary mastery. This research was a quasi-experimental research. The population is the whole class VIIISMPN1Selong. Sampling was done by random sampling technique for the population in the unit class. Samples of study were class VIIIA as a control class that uses conventional teaching (lectures) and VIIIB as an experimental class that use media movie with subtitles. The data were obtained through pre test to know the students’ ability. Statistical test used to test the hypothesis was Mann Whitney U test with a normal curve approach Z performed on the data post-test. Data post-test showed at the 0.05significance level, the value of Z table=1.99, and Z count (3.25)>Z table (1.99). Because Z count is greater than Z table, then Ha accepted and Ho is rejected. It was found that the result of this research was the using of media movie with English subtitles was effective in increasing knowledge of vocabulary in class VIII SMAN 1Selong Lombok Timur in the academic year of 2018/2019.